Supermarkets made in. Connections, consumption and appropriations. United States and Colombia (20th century) (2017)
The main purpose of this article is to conduct an analysis of a specific space of consumption: the supermarket. Relationships and connections of some Colombian traders and supermarket owners will be studied (those with experiences upon the North American trade and commerce), as well as the learning strategies and processes of differential appropriation that was mandatory for the introduction of these trading and consumption spaces in several cities of the country. The methodology used was based upon the analysis and revision of primary and secondary sources, from the approach of the connected histories. As a result, this article asserts that the Colombian merchants had an active participation through their own local experiences and that they contributed to complement the accumulation of knowledge about supermarkets; a knowledge that was already set in different places of the world, from the middle of the 20th Century. © 2017, Universidad de los Andes, Bogota Colombia. All rights reserved.